Left Main Coronary Artery Bifurcation Coronary Intervention in a Patient with Achondroplasia with Multivessel Coronary Artery Disease - Debasish Das; Anindya Banerjee; Abhinav Kumar; Tutan Das; Shashikant Singh; Jaideep Das Gupta; Manaranjan Dixit (Indian Journal of Medical Specialities)
We report a rare case of critical coronary artery disease in a 62-year-old male with achondroplasia. There is a paucity of case reports of association of achondroplasia with coronary artery disease. Left main coronary artery (LMCA) bifurcation lesion carries the highest risk of mortality out of all types of coronary artery lesions and patients with achondroplasia have two-fold more mortality as compared to the general population. That is why achondroplasia patients may be having more sudden cardiac death with the most catastrophic LMCA bifurcation lesion before they undergo revascularization. It may be the plausible explanation behind no literature description of LMCA bifurcation lesion in patients with achondroplasia. Our case is the first literature description of LMCA bifurcation lesion with successful intervention in achondroplasia. The present case will also provide a detailed insight into the association of achondroplasia with coronary artery disease without the presence of conventional cardiac risk factors.